Reconstructing the Pattern of Islamic Education during the al-Khulafāʾ al-Rāsyidūn Period and Its Relevance to the Indonesian Educational Context - Faisal Amir Toedien; Eva Dewi; Sutarmo Sutarmo (Bulletin of Indonesian Islamic Studies, 2025)
Islamic education has been a main pillar in shaping Islamic civilization since the time of the Prophet Muhammad, and it was further developed by caliphs after him. The period of the al-Khulafāʾ al-Rāsyidūn (632–661 CE) marked a significant phase in the continuation and advancement of Islamic education after the revelation ended. This article aims to describe the educational patterns and analyze the role of each caliph in the development of education. The research employs a qualitative method with a literature review approach, examining primary and secondary sources such as historical texts, tafsir works, and academic literature. The study focuses on the educational policies and contributions of Abū Bakr aṣ-Şiddīq, ‘Umar ibn al-Khaṭṭāb, ‘Uśmān ibn ‘Affān, and ‘Alī ibn Abī Țālib. The findings reveal that each caliph adopted strategic approaches in fostering education, including the codification of the Qur'an, the establishment of knowledge institutions, and the promotion of critical thinking. The results show that the Islamic education system was structured and transformative from the beginning. This study contributes to the academic discourse on Islamic educational history and offers insights for developing educational models rooted in authentic Islamic values. These findings are essential as a historical foundation for designing contemporary Islamic education.